Accounting for non-accounting students: what affects their performance? - Ismail, Suhaiza; Kasim, Nurkamariah (2011)

(untitled)
This study aims to examine the factors affecting the examination performance of non-accounting students in completing an accounting course, that is, Management Accounting. A questionnaire survey was administered to a total of 147 non-accounting students who enrolled in a Management Accounting course for a semester. The factors considered are gender, prior academic performance, year of study and learning approaches adopted which include deep, surface and strategic approaches. Using multiple regression analysis, the results reveal that prior academic performance and year of study have a positive significant impact on performance while the surface approach of learning has a negative significant impact on the performance of the students. This present study mainly focused on the overall performance of the students and did not investigate the effect of the factors on the performance of the various assessment components in Management Accounting course. The findings imply that the Management Accounting course should be offered to higher level non-accounting students. In addition, for completing the course with good results, the surface approach to learning should be avoided. The present study is unique as it considers the students performance in a subject that is not the main discipline of the students (i.e., accounting course for non-accounting students).